EFFECTIVENESS OF PHYSICAL THERAPY IN MILITARY SERVANTS AFTER ARTHROSCOPIC TREATMENT OF KNEE JOINT INJURIES (Physical Culture and Sport: Scientific Perspective, 2025)
Knee injuries are one of the most common problems among the military, which is due to the high level of physical exertion, the specifics of combat training and service conditions. Arthroscopic treatment of such injuries is a modern and widely used method that provides minimal invasiveness and promotes rapid restoration of joint function. Purpose of the study: to determine the effectiveness of physical therapy for military personnel after arthroscopic treatment of knee injuries. Research methods. The work used methods of the theoretical level of research: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodological literature; empirical level (goniometry and anthropometry); methods of mathematical statistics. Results of the work. A feature of the treatment of knee injuries in the military is the need for rapid restoration of joint function to ensure the ability to perform professional tasks. Modern treatment methods, such as arthroscopy, allow for effective elimination of the consequences of injuries with minimal surgical intervention. Comparison of the results of rehabilitation measures after knee arthroscopy in both groups confirmed the effectiveness of the developed physical therapy program. During rehabilitation, the experimental group showed significant improvements in the range of motion of the knee joint compared to the control group in the direction of flexion and extension. At the end of the study, statistically significant differences were found between the main and control groups. Flexion in the knee joint in patients of the main group was significantly greater by 25.74 degrees (p
Keywords: injuries; physical therapy; knee joint; arthroscopy